Использование энергии СВЧ для повышения эффективности хранения зерна - Волевахин, Г. М.; Контарь, А. А.; Кухтина, Н. Н. (ХНУРЭ, 2009)
The research of possible use of microwave frequency energy for the purpose of grain storage improvement has been carried out in this work. The radiation with a wave length of 12 centimeters and the power density of 280-300 W•kg/sec reduces vermin growth to 50-70% depending on the grain humidity. The power density of 400 W• Kg/sec totally eliminate further vermin propagation. Perspectives of pesticides replacement with a microwave frequency processing for food quality enhancement are also discussed in this thesis. Развитие современной техники в области создания СВЧ генераторов позволяет создавать установки модульного типа на различную мощность. В связи с этим расширяются перспективы внедрения обеззараживания зерна на элеваторах и в других хранилищах под воздействием энергий СВЧ диапазона, что приведет к значительному сокращению применения ядохимикатов вплоть до их полного исключения.
Keywords: СВЧ генератор; обеззараживание зерна; элеватор